2018
DOI: 10.3892/ijmm.2018.3763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autophagy on allodynia, hyperalgesia and astrocyte activation in a rat model of neuropathic pain

Abstract: Primary damage or dysfunction of the nervous system may cause or initiate neuropathic pain. However, it has been difficult to establish an effective treatment for neuropathic pain, as the mechanisms responsible for its pathology remain largely unknown. Autophagy is closely associated with the pathological process of neurodegenerative diseases, neuropathic injury and cancer, among others. The aim of the present study was to examine the changes in the autophagy-lysosomal pathway and discuss the effects of autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 68 publications
3
35
0
1
Order By: Relevance
“…Wipi2, which is involved in autophagy in DRG neurons (Stavoe et al, 2019), a process 281 argued to reduce the pain associated with sciatic nerve injury (Chen et al, 2018). PEP1 282 neurons selectively induce Ano1, which promotes pain hypersensitivity (Lee et al, 2014).…”
Section: Classification Of Neuronal Subtypes After Axotomy 199mentioning
confidence: 99%
“…Wipi2, which is involved in autophagy in DRG neurons (Stavoe et al, 2019), a process 281 argued to reduce the pain associated with sciatic nerve injury (Chen et al, 2018). PEP1 282 neurons selectively induce Ano1, which promotes pain hypersensitivity (Lee et al, 2014).…”
Section: Classification Of Neuronal Subtypes After Axotomy 199mentioning
confidence: 99%
“…In a previous study, we found that Rab7 contributes to the processing of inflammatory pain in a redox-dependent manner [ 6 ]. Moreover, expression of Rab7 is upregulated after peripheral nerve injury [ 7 ] and Rab7-mediated lysosomal targeting of µ-opioid receptors leads to a loss in opioid antinociception in diabetic neuropathic pain [ 8 ]. Furthermore, trafficking of the neurokinin 1 receptor (NK1R) in sarcoma virus-transformed rat kidney epithelial cells was found to be controlled by Rab5a [ 9 ] and expression of Rab23 was induced in an inflammatory pain model [ 10 ], suggesting that, also, other Rab proteins contribute to the processing of pain.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral or central nerve damage can induce neuropathic pain (1,2). Common abnormal signs of neuropathic pain are hyperalgesia (exaggerated pain perception in response to noxious), allodynia (pain perception in response to non-noxious stimuli) and psychological disorders such as anxiety (3,4). In most of the pharmacological studies along with neuropathic pain management, the effects of different compounds on these behavioral parameters are investigated (5).…”
Section: Introductionmentioning
confidence: 99%